Konsumsi Junk Food dan Hipertensi pada Lansia di Kecamatan Kasihan, Bantul, Yogyakarta - Rantiningsih Sumarni; Edi Sampurno; Veriani Aprilia (Alma Ata University Press, 2015)
The risk of hypertension increases in line with a changes in modern lifestyle. Elderly tends to select food such as junk food with high calories, and fat, but low in ﬁ ber and other nutrients. Junk food contains high amounts of sodium that can increase the volume of blood in the body, so make stronger heart blood pumps and cause the higher blood pressure (hypertension). The purpose of this study was to identify the relationship between junk food consumption and hypertension in elderly in Kasihan sub-district Bantul, Yogyakarta. This was an observational analytic study with cross sectional design. The samples were 100 elderly lives in Kasihan sub-district Bantul, Yogyakarta. The results showed that there was relationship between the consumption of junk food and hypertension. Respondents who suffered from hypertension were 49 (67.1%) who often consumed junk food and 24 respondents (32.9%) who rarely consumed junk food. Respondents who did not undergo hypertension were 9 respondents (33.3%) that often consumed junk food and 18 respondents (66.7%) that rarely consumed junk food. In conclusion, there was a relationship between junk food consumption and hypertension in elderly. Risk of hypertension in respondents who consumed more often junk food were 4.083 times higher than them who rarely consumed junk food.